3D mobile navigation for dynamic users interaction - Mantoro, Teddy; Abubakar, Adamu; Ayu, Media Anugerah (2011)
Interactive navigation within an environment with the aid of 3D map of the environment in mobile devices’ provides end users with mobility support and improves mobility services’ efficiency and effectiveness. Accurate and ubiquitous multi-user localization is one of the key prerequisites for realizing the potential of interactive navigation based services, which is the motivation of this study. Unfortunately, the predominant 3D mobile navigation system does not provide interactions of many users and the shortest paths. Users cannot be aware of other users navigating within that environment using the same system on their mobile devices at the same time. The objective of this paper is to presents an interactive 3D mobile navigation system for an optimal solution in finding the shortest path and providing multi-user awareness, through building the system and undertaken an experiment. The result guarantees a minimum cost for achieving the full coverage of the environment and connectivity to the target position for multiple users at the same time. The approach is unique because it provides visualization of 3D map model in mobile devices’ which assists users to navigate to a target location and being aware of other users (who are using the same system).